Seroprevalensi Penyakit Tetelo pada Peternakan Itik dan Pasar Galiran di Kabupaten Klungkung, Bali (NEWCASTLE DISEASE SEROPREVALENCE IN LIVESTOCK DUCK AND MARKETS GALIRAN OF KLUNGKUNG RECIDENCE, BALI) - Yuliana, I Komang Wahyu; Kencana, Gusti Ayu Yuniati; Suartha, I Nyoman (Jurnal Veteriner, 2015)
Ducks are one of the birds that play a role in the spread and transmission of Newcastle disease virus.Newcastle disease infection in ducks are rarely accompanied by clinical symptoms, so the ducks couldpotentially spread the disease to other birds. In general, the distribution of ducks is going from farm toMarket Poultry and vice versa. The aim of this study was to determine the seroprevalence Newcastledisease infection in ducks reared on farms and sold at market Galiran Klungkung regency. The sampleused in this study was serum unvaccinated ducks ND. The samples used were 420 samples taken from thefarm and from Klungkung Galiran Market from March to August 2012.Serum samples were tested for thepresence of NDV antibody by using hemagglutinationtest(Haemaglutination Inhibition Test / HI test) atthe Biomedical Laboratory of the Faculty of Veterinary Medicine Udayana University. The results showedthat the seroprevalence Newcastle disease virus in ducks in Galiran Market were 33.3% and in farmsamounted to 46.2%. There are differences in seroprevalence Newcastle disease (p <0.05) in March, June,and August. Overall seroprevalence in Galiran Market and Newcastle disease in livestock in Klungkungregency equal to 39.8%. It can be concluded that Newcastle disease seroprevalence in Klungkung regency isquite high and might be potentially transmit the virus to other poultry. Therefore, periodic monitoring isnecessary as an effort to early prevention.
Keywords: Newcastle disease, seroprevalence, livestock, Galiran market, ducks